Physical and chemical degradation of littered personal protective equipment (PPE) under simulated environmental conditions. (May 2022) - De-la-Torre, Gabriel Enrique; Dioses-Salinas, Diana Carolina; Dobaradaran, Sina; Spitz, Jörg; Keshtkar, Mozhgan; Akhbarizadeh, Razegheh; Abedi, Delaram; Tavakolian, Abbasali
Abstract: Investigations of the physicochemical degradation of personal protective equipment (PPE) under controlled environmental conditions are largely lacking. Here the chemical and physical changes of face masks and gloves (recovered from the marine environment) were evaluated after exposure time up to 60 days of simulated environmental conditions. The results suggested that the polymer backbone of PPE suffers typical changes induced by sun exposure. Changes in the intensity of diffraction peaks indicated shifts in the crystallinity of PPE, possibly altering their thermal behavior. Signs of physical degradation in PPE, such as ruptures, and rough surfaces, which exacerbated over time were also detected. Additionally, signals of some elements of concern, such as Cu and Mo, and elements typically found in seawater were detected. The results of this study allowed us to better understand the degradation of typical PPE items in the marine environment, ultimately resulting in the release of microplastics and chemical contaminants. Graphical abstract: Unlabelled Image Highlights: Physicochemical changes of PPE were assessed in simulated environmental conditions. Polymer backbone of PPE suffers typical changes induced by sun exposure. Intensity of the diffraction peaks showed shifts in the crystallinity of PPE. Clear sign of physical degradation (cracks, rough surfaces) in PPE over time Signals of elements such as Cu, Mo, as well as elements normally found in seawater